Patterns of innovation networks formation in a closed-cycle economy - A. I. Shinkevich; F. F. Galimulina; S. A. Bashkirtseva (Вестник университета)
The relevance of the study is due to the poor knowledge of the problems of the formation of innovation networks in a closed-cycle economy. Against this background, the purpose of the study is determined – to develop provisions that develop the methodology of managing innovation networks in the context of a closed-loop economy and allow identifying patterns of formation of innovation networks. In this regard, attempts have been made to assess the patterns of development of network interactions within the framework of innovation activities of territories. Using the example of European countries, the interrelation of indicators of cooperation in the field of innovation and indicators of a cyclical economy is evaluated, as a result of which countries of advanced, transitional and catching-up types of development are identified. Based on the proposed author’s methodology, a matrix of positioning territories according to the degree of interconnection of innovation networks and closed-cycle economic indicators is constructed, 4 development trajectories are identified. The methodology for assessing the aggregate index differs by taking into account the reference proportions of cooperation, allows for a differentiated approach to the support of territories, is universal and can be applied by public authorities in the development and refinement of spatial development strategies.